Role of Social Support for Multi-Drug Resistant Tuberculosis Patients’ Treatment Adherence in a Specialized Hospital - Rozario, Mukta; Islam, ANM Shamsul; Khanam, Fahmida (Journal of Preventive and Social Medicine, 2025)
Background: Multi-drug resistant tuberculosis (MDRTB) is an emerging major public health problem globally and an obstacle for effective global TB control. Social support for MDRTB patients is important drivers for the successful treatment adherence of the patients. The objective of this study was to assess the role of social support for MDRTB patient’s treatment adherence in a specialized hospital. Methods: This descriptive type of cross-sectional study was carried out among MDRTB patients within the period of January to December 2017 in National Institute of Diseases of the Chest & Hospital (NIDCH) Mohakhali, Dhaka. A total of 120 respondents MDRTB patients were selected purposively. Data was collected by face to face interview of respondents using semi structured questionnaire and Social Support Rating Scale (SSRS) and treatment record review. Data was analyzed by using SPSS (Statistical Package for Social Science) software version 20. Results: The most prevailing 40% patients were in age group from 21-30 years. The mean age of the respondent was 31.6 years. The respondents 4.5% (n=3) were separated from their spouse due to MDR TB. The average social support score of each MDR-TB patient was 26.82±4.02. The respondents who were elderly, low family income and male respondents, had received lower social support (P=0.043, P=0.032 and 25.90>28.16, P=0.002 respectively) from their surroundings. Many respondents had not received higher social support in this study. Conclusion: In this study MDR TB patients were found to have a low level social support. Patients’ self-isolation may contribute to a decrease in the amount of support they receive from their surroundings. There is need to formulate strategy that includes motivational counseling and social support mobilization for treatment adherence. JOPSOM 2024; 43(2): 10-16